Conceptualizing meaningful education: The voices of indigenous parents of young children. (September 2019) - Matengu, Marika; Korkeamäki, Riitta-Liisa; Cleghorn, Ailie
Abstract: The current study was conducted in rural Namibia by interviewing seventeen parents of pre-primary learners in an indigenous community. Interview data was analyzed qualitatively to identify advantages of education that parents found worth pursuing and supporting. The study revealed that current education models do not correspond to indigenous understanding of meaningful education, which is to equip children to effectively transition from the indigenous community to the future in the modern world. The findings suggest that parents' freedom to choose and influence education they find meaningful is limited to dominant education models mainly informed by the Global North. The development of indigenous education requires building meaningful parental participation that informs educational models. Drawing from theories of social justice, this study responds to strategies advocated to solve the quality crisis in educationally marginalized contexts and the challenge of education planners to ensure that education becomes a catalyst for social justice.